NFT (Non-Fungible Token) e a arte digital: tensionamentos entre reprodutibilidade técnica, autenticidade e aura - Zimmer, Anderson (Universidade do Vale do Rio dos Sinos, 2022)
This investigation aims to understand how NFTs tension the authenticity and aura of technical images, and how they update these concepts, brought by Vilém Flusser (2002) and Walter Benjamin (2017), in the technological context of digital art, highly reproducible, ando of increasingly liquid consumption, detached from material objects (BAUMAN, 2008). The research is a case study, designed and constructed through a cartographic movement, where the current scenario of non-fungible tokens was investigated, taking as empirical object six highlighted images from the work of art Everydays: The First 5000 Days, composed of five thousand individual images. A piece created by artist Beeple, who produces purely digital images for commercialization on the blockchain. The investigation resulted in a clarification on NFTs in relation to their properties as technical images, their artistic value and their commercial applications. This research, in addition to enabling the updating of the conceptual debate brought by the authors, allows us to understand the new communicational dynamics surrounding digital art and technical images, such as: the presentation of the creative process on the web; the cult of images and their exposure based on the circulation of meanings on web interactions; the resignification of spaces and ways of art consumption, where reproducibility and uniqueness are articulated. In this way, these findings can contribute to future research aimed at working with this aspect of image investigation.
Keywords: Autenticidade; Aura; Imagem técnica; NFT; Arte digital; Consumo líquido; Blockchain; Authenticity; Technical image; Digital art; Liquid consumption